The lower limb perforator veins in normal subjects - Hill, Brigid G.; van Rij, André M. (Journal of vascular surgery. Venous and lymphatic disorders (New York, NY), 2022)
With the developments in vascular ultrasound technology, the opportunity has arisen to examine in greater detail the distribution and behavior of the perforators in normal lower limbs and the implications in understanding their normal role. The lower limbs of 20 healthy participants free of any cardiovascular or venous disease were examined. The anatomical characteristics and distribution as well as the functional features of all ultrasound-detectable lower limb venous perforators were evaluated in these normal limbs. Perforator flow was tested at rest, supine, sitting, standing, and with exercise. Comparisons were made between standard augmentation and isometric foot plantar flexion. Twenty individuals (13 females, 7 males; mean age, 36.9 ± 12 years) participated in the study. On average each limb had 14.2 (range, 8-21) perforators identified by ultrasound examination, with an average size of 1.3 ± 0.56 mm (range, 0.4-3.5 mm), most in the medial calf and those in the lower third were larger. On ultrasound examination, the valves were observed only within these larger direct perforators (17%; 18/105). All maneuvers resulted in flow which was only from superficial to the deep system and no two-way flow was observed. Spontaneous flow at rest occurred in a small proportion, but treadmill walking led to the recruitment of most perforators with spontaneous pulsatile flow at greatly increased velocities. The estimated total perforator volume flow could be increased by up to five-fold and accounting for as much as 80 mL/min in a leg. Isometric foot plantar flexion stopped any spontaneous flow and, on relaxation, resulted in a reproduceable short burst of inflow in the calf perforators. Augmentation by calf or foot cuff compression produced a brief variable inward, flow but this flow did not correlate with the perforator flow, with the more physiological maneuvers of isometric foot plantar flexion and exercise. This study has shown that normal perforator veins in the leg are unidirectional from superficial to deep veins. Although few perforators have spontaneous flow at rest, most are recruited with exercise to substantially increase spontaneous perforator flow secondary to the increased skin blood flow. The augmentation maneuver is not comparable with more physiological activity. These normal features should be taken into account in the assessment of the abnormal perforator.